Analisis Penggunaan Internet Terhadap Hasil Belajar Siswa - Febriana, Febriana; Harahap, Nurul Febriyani; Sulvina, Ardilla; S, Aulia Intan Rachmawati; Siregar, Tiur Malasari (Jurnal Ilmiah Wahana Pendidikan, 2024)
Technological developments play a very important role and contribute to the direction of development in the world of education. In the history of educational development, information technology is part of the media used to convey scientific messages to many people. One of the internet users provided by schools is that the internet will become part of a teaching and learning process. The research method used is a qualitative descriptive method with a library study approach, which is used to search and collect relevant information and data from various books, journal articles and internet media relating to the influence of Internet use on student learning outcomes. The number of internet users in Indonesia reached 213 million people, or 77% of Indonesia's total population, which amounted to 276.4 million people at the beginning of the year. The number of internet users in the country increased 5.44% year on year. The number of Indonesian internet users will only reach 202 million in January 2022. It is hoped that the development of the internet in the teaching and learning process can stimulate students' interest in learning and encourage students to participate in the teaching and learning process. By developing creative and innovative learning and utilizing existing technology, it is an effort to create and foster interest in learning and attract students' attention in the teaching and learning process.